Prototype Pengukuran Kadar Alkohol dan Co Pada Ruangan Laboratorium Pendidikan Kimia Berbasis IoT - Al Aziz, Vindy Rova Dwiki; Zarory, Hilman; Son Maria, Putut; Faizal, Ahmad (Building of Informatics, Technology and Science (BITS), 2024)
Technological advancements, particularly the Internet of Things (IoT), have significantly impacted various sectors, including chemical laboratories. This research aims to design a device for detecting Alcohol and Carbon Monoxide (CO) levels in the Chemistry Education Laboratory at UIN SUSKA RIAU. The device uses MQ-3 and MQ-135 sensors connected to an ESP32 microcontroller, featuring voice notifications and integration with the Blynk application for real-time monitoring. The design includes key components such as a power supply, buzzer, speaker, DFPlayer Mini, LED, and 16x2 LCD. Hardware and software testing were conducted to ensure the device's reliability and durability. The test results showed variations in CO and Alcohol levels in the laboratory over five days. The MQ-135 sensor indicated a significant increase in CO levels on Tuesday with an average of 55.4 PPM, while the MQ-3 sensor recorded the highest Alcohol levels on Friday with an average of 2%. These variations were due to intensive practicum activities and suboptimal air circulation. The implementation of this device successfully detected and transmitted air quality data accurately and quickly through the Blynk application. The research results emphasize the importance of monitoring and controlling air quality in laboratories to ensure a safe and healthy environment for users. The use of sensors integrated with IoT has proven effective in enhancing monitoring quality and providing real-time data that can be accessed remotely, contributing positively to supporting safer learning activities in chemical laboratories